A numerical study on the performance and emission of a container ship propulsion system. (2016) - Tu, Huan
In this paper, the investigation of the performance and emission parameters of a container ship propulsion system is carried out by using a model implemented in Matlab/Simulink environment. The ship propulsion system model is developed in a modular approach and composed of sub-models representing the diesel engine, the shaft system, the propeller and the ship, respectively. Initially, the engine model is validated using the experimental data. Then, simulation of the ship propulsion system at steady state operating points on various resistance curves is performed. The variation of the propulsion system performance and emission parameters over the ship operating range is presented and discussed. Finally, the application of the derived results is exemplified in the case of the speed optimisation for the container ship operating in a specific route in order to minimise the fuel consumption and emissions.